Identifying the Molecular Mechanisms Contributing to Progression, Metastasis, and Death in Low-grade Non–muscle-invasive Bladder Cancer: A Case Report - Sarah Weiß (European Urology Open Science, 2021)
Transitional cell carcinoma of the bladder is a common malignancy with an estimated 549 393 new cases occurring in 2018 alone. Both non–muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) show high recurrence and progression rates, and therefore impose a great burden on patients and health care systems. Current risk stratification and therapy strategies are predominantly based on clinical and histopathological findings for tumor stage and grade. The chemoresistance and metastasis of low-grade tumors suggest an incomplete understanding of disease mechanisms, despite numerous studies on differentiating molecular subtypes of bladder cancer to identify tumor drivers and potential therapeutic targets. We present a highly unusual course for a low-grade bladder tumor leading to metastasis and death, for which we used postmortem histopathological and molecular analyses to evaluate targetable alterations in key signaling pathways driving the underlying tumor biology.